2017
DOI: 10.17269/cjph.108.5875
|View full text |Cite
|
Sign up to set email alerts
|

Child development in rural Ghana: Associations between cognitive/language milestones and indicators of nutrition and stimulation of children under two years of age

Abstract: OBJECTIVES: Two studies aimed to assess the provision of nutrition and psychosocial stimulation in the home and to examine associations between mental development and nutrition and stimulation using a validated measure of development milestones. METHODS:The first study consisted of secondary analyses on health and nutrition data from 1081 mother-child pairs (the children aged 0-12 months) and their households in Ghana's Eastern Region. For the second study, the Ghana Milestones Measure, consisting of items ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…A sub-sample from a larger cohort, recruited as previously described was selected for this study. In brief, 1095 households were recruited for a cluster randomized controlled community trial [ 22 ]. Subjects for this study were recruited from the control arm.…”
Section: Methodsmentioning
confidence: 99%
“…A sub-sample from a larger cohort, recruited as previously described was selected for this study. In brief, 1095 households were recruited for a cluster randomized controlled community trial [ 22 ]. Subjects for this study were recruited from the control arm.…”
Section: Methodsmentioning
confidence: 99%
“…Of the seven cross‐sectional studies reporting associations between Hb concentration and LAZ, six found a significant association with LAZ . Of the five cross‐sectional studies reporting associations between Hb and WAZ, four found significant associations . For instance, Aubuchon‐Endsley et al .…”
Section: Resultsmentioning
confidence: 99%
“…Eight cross‐sectional studies reported associations between Hb and mental or language development; four of which found significant associations . For instance, in older Egyptian children 2–5 years of age, Khalifa et al .…”
Section: Resultsmentioning
confidence: 99%
“…Items were scored as 1 if the child had performed this activity and 0 if the child had not yet performed it. This measure has been validated in India, Burkina Faso, Kenya and Ghana ( 28 , 30 32 ) .…”
Section: Methodsmentioning
confidence: 99%